A search for pair-produced resonances in four-jet final states at √s = 13 TeV with the ATLAS detector - Alconada Verzini, María Josefina (2018)
A search for massive coloured resonances which are pair-produced and decay into two jets is presented. The analysis uses 36.7 fb−1 of √s = 13 TeV pp collision data recorded by the ATLAS experiment at the LHC in 2015 and 2016. No significant deviation from the background prediction is observed. Results are interpreted in a SUSY simplified model where the lightest supersymmetric particle is the top squark, ~t , which decays promptly into two quarks through R-parity-violating couplings. Top squarks with masses in the range 100 GeV < m~t < 410 GeV are excluded at 95% confidence level. If the decay is into a b-quark and a light quark, a dedicated selection requiring two b-tags is used to exclude masses in the ranges 100 GeV < m~t < 470 GeV and 480 GeV < m~t < 610 GeV. Additional limits are set on the pair-production of massive colour-octet resonances.